Early and late mortality following unscheduled admissions for severe liver disease across England and Wales - Roberts, Stephen E. (Aliment Pharmacol Ther, 2019)
BACKGROUND: There is a known shortfall in hepatology service resources across England and Wales. AIM: To investigate early and late mortality following unscheduled admissions for severe liver disease, overall and by cause of death, and to determine how mortality is related to admissions to transplant centres, transplant surgery, hospital size, consultant specialty, patient socio‐demographics, seasonal and geographical factors. METHODS: Cohorts of people with a first unscheduled admission for severe liver disease across England and Wales from 2004, based on record linkage of national inpatient and mortality data. FINDINGS: Mortality for alcoholic liver disease and hepatic failure was 23.4% and 35.4% respectively at 60 days and 61.8% and 57.1% at 5 years. Standardised mortality ratios (SMRs) were extremely high at 60 days (184 and 117 respectively) and remained highly increased at 5 years (16.7 and 6.3). Mortality at 5 years was most elevated from liver disease, viral hepatitis and varices. The 60‐day mortality was significantly lower for patients seen by consultant hepatologists and gastroenterologists. Both early and late mortality were significantly reduced for patients admitted to transplant centres or larger hospitals, who received a liver transplant, or were resident in London. Early mortality was significantly higher for patients admitted in winter and autumn, while elevated mortality among the most vs least deprived quintile increased with longer follow‐up. CONCLUSIONS: The study shows a very poor prognosis for people with unscheduled hospitalisation for severe liver disease. The findings suggest that access to specialist expertise and services improves survival, both in the short and long term.